Development Media Groups - UK - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Centre for World Development Education (CWDE) was founded in 1977 to raise the level of awareness and understanding in Britain of major development issues in the Third World. It grew out of the longer-standing education unit of the Voluntary...